A Taste for Language : Literacy, Class, and English Studies. - Watkins, James Ray (Studies in writing & rhetoric., 2009)
"This is a book about the American Dream as it has become embodied in the university in general and in the English department in particular," writes James Ray Watkins at the start of A Taste for Language: Literacy, Class, and English Studies. In it, Watkins argues that contemporary economic and political challenges require a clear understanding of the identity of English studies, making elementary questions about literacy, language, literature, education, and class once again imperative. A personal history of university-level English studies in the twentieth century, A Taste for Language c